Reciprocal threats in multimarket rivalry: staking out ‘spheres of influence’ in the U.S. airline industry - Gimeno, Javier (Strategic Management Journal, 1999)
The paper investigates the outcomes of multimarket competition among U.S. scheduled airlines when the interests and positions of the airlines differ in the mutually contested markets. Asymmetry in territorial interests provides multimarket competitors with footholds in important markets of their rivals, which can be used to deter the behavior of the rivals in other markets. Evidence suggests that airlines use footholds in their rivals’ important markets (particularly in their hubs) to reduce the competitive intensity of those rivals in the airlines’ own important markets (their hubs), and sustain their dominant positions (or spheres of influence) in those markets. Copyright© 1999 John Wiley & Sons, Ltd.